Benson Relaxation and Hypnosis in Quality of Elderly Sleep - Kastubi Kastubi; Rini Ambarwati (Health Notions, 2018)
The process of degeneration in the elderly resulting in the quantity of sleep the elderly will be reduced so as not achieved adequate sleep quality. This study aimed to analyze the influence of Benson relaxation and hypnosis to improve the fulfillment of sleep needs and control of elderly blood pressure, with experimental design that is Pretest - Posttest with Control Group. The subjects of the study were elderly at Integrated Service Post (Posyandu) of Elderly who had sleep disorder, selected by simple random sampling technique. Data were collected by using questionnaires. Benson relaxation and hypnosis were performed 2 times a week for 2 weeks. The collected data were analyzed descriptively in the form of mean and standard deviation, then analyzed using Wilcoxon and Mann Whitney test. The results showed that insomnia could be derived by implementing Benson relaxation, hypnosis, hypnosis + relaxation. Based on research results recommended that health care institutions use relaxation techniques and hypnosis as one of the standard operational procedures in overcoming insomnia problems. Keywords: Benson Relaxation, Sleep, Hypnosis